Enrichment analysis of Alu elements with different spatial chromatin proximity in the human genome. Issue 4 (10th February 2016) - Gu, Zhuoya; Jin, Ke; Crabbe, M James C; Zhang, Yang; Liu, Xiaolin; Huang, Yanyan; Hua, Mengyi; Nan, Peng; Zhang, Zhaolei; Zhong, Yang
Abstract: Transposable elements (TEs) have no longer been totally considered as "junk DNA" for quite a time since the continual discoveries of their multifunctional roles in eukaryote genomes. As one of the most important and abundant TEs that still active in human genome, Alu, a SINE family, has demonstrated its indispensable regulatory functions at sequence level, but its spatial roles are still unclear. Technologies based on 3C (chromosome conformation capture) have revealed the mysterious three-dimensional structure of chromatin, and make it possible to study the distal chromatin interaction in the genome. To find the role TE playing in distal regulation in human genome, we compiled the new released Hi-C data, TE annotation, histone marker annotations, and the genome-wide methylation data to operate correlation analysis, and found that the density of Alu elements showed a strong positive correlation with the level of chromatin interactions (hESC: r = 0.9, P < 2.2 × 10 16 ; IMR90 fibroblasts: r = 0.94, P < 2.2 × 10 16 ) and also have a significant positive correlation with some remote functional DNA elements like enhancers and promoters (Enhancer: hESC: r = 0.997, P = 2.3 × 10 −4 ; IMR90: r = 0.934, P = 2 × 10 −2 ; Promoter: hESC: r = 0.995, P = 3.8 × 10 −4 ; IMR90: r = 0.996, P = 3.2 × 10 −4 ). Further investigation involving GC content and methylation status showed the GC content of Alu covered sequences shared a similar pattern with that of the overall sequence, suggesting that Alu elements also function as the GC nucleotide and CpG site provider. In all, our results suggest that the Alu elements may act as an alternative parameter to evaluate the Hi-C data, which is confirmed by the correlation analysis of Alu elements and histone markers. Moreover, the GC-rich Alu sequence can bring high GC content and methylation flexibility to the regions with more distal chromatin contact, regulating the transcription of tissue-specific genes.